Wideband antenna arrays for mmWaves - Caiado, João Bernardo Santos (2019)
In this dissertation seven wideband log-periodic arrays were developed. One of the arrays operates in the C band of frequency, while the others operate in the mmWaves band. The six arrays constructed for the mmWaves distinguish themselves by the height of the substrate and the number of patches. Two different heights were used and for both arrays with five, seven and nine elements were developed. The bandwidth was influenced by the changes made in the arrays. In the case of the C band array the bandwidth obtained was 572 MHz. In the arrays developed with a thinner substrate, for the mmWaves, the bandwidths obtained were 5.388 GHz, 6.873 GHz and 9.266 GHz, for the five, seven and nine elements arrays, respectively. Comparatively, the arrays made with a thicker substrate enhanced the bandwidth to 6.899 GHz, 8.282 GHz and12.07 GHz, respectively.